Beaked whale strandings on the coast of Australia in comparison to those of other cetaceans - Hamilton, L. J.; Lindsay, K. (J. Cetacean Res. Manage., 2023)
Beaked whale (Ziphiidae) strandings on the coast of Australia are examined in comparison to five other odontocete (toothed whale) species and two mysticetes (baleen whales) representative of non-Ziphiids found stranded in Australian waters. Ninety percent of reported beaked whale strandings involve a single animal. Seven beaked whale stranding events of three or more individuals have been recorded from 1871 to 2010, with a maximum in any event of 6. The five non-Ziphiid odontocetes had maximum numbers in a stranding of 13, 51, 65, 200, and 250, and a combined total of 66 events with 10+ in a stranding. The mysticetes had almost exclusively single strandings. Similar trends for the Ziphiids and other cetaceans are generally observed worldwide, although larger numbers of Ziphiids have stranded elsewhere. Continental scale geographical stranding patterns are similar for the Ziphiids, the five non-Ziphiid odontocetes, and the two mysticetes, although not for the same reasons. Reported strandings predominantly occurred around the southern half of Australia south of 20°S. On average around three times as many beaked whale stranding events per month occurred for the period January to April than for July to December. The monthly trend for beaked whale strandings follows the seasonal cycle of sea temperatures, indicating a relation to oceanic phenomena, rather than to the often invoked effect of increased observer effort in months with warmer air temperatures. Some single and dual beaked whale strandings which include a female may be related to use of shallow sheltered waters for calving and subsequent resting.